2016
DOI: 10.1037/xge0000168
|View full text |Cite
|
Sign up to set email alerts
|

Highly accurate prediction of emotions surrounding the attacks of September 11, 2001 over 1-, 2-, and 7-year prediction intervals.

Abstract: In the aftermath of a national tragedy, important decisions are predicated on judgments of the emotional significance of the tragedy in the present and future. Research in affective forecasting has largely focused on ways in which people fail to make accurate predictions about the nature and duration of feelings experienced in the aftermath of an event. Here we ask a related but understudied question: can people forecast how they will feel in the future about a tragic event that has already occurred? We found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…In both studies, across participants, moderately high correlations were found between forecast and experienced emotional intensity ( r = .71 in Study 1 and .67 in Study 2). This finding is consistent with recent research showing that the magnitude of forecasting bias depends on the feature of emotion being forecast, and that people are fairly accurate when forecasting the intensity of their future emotional experience (Doré et al, 2016; Lench et al, 2019; Levine et al, 2012). Despite being fairly accurate, participants in Study 1 overestimated the emotional impact of receiving a lower than expected grade or an expected grade, consistent with a large body of research showing an impact bias in affective forecasting (Gilbert et al, 2002; Wilson & Gilbert, 2003).…”
Section: Discussionsupporting
confidence: 92%
“…In both studies, across participants, moderately high correlations were found between forecast and experienced emotional intensity ( r = .71 in Study 1 and .67 in Study 2). This finding is consistent with recent research showing that the magnitude of forecasting bias depends on the feature of emotion being forecast, and that people are fairly accurate when forecasting the intensity of their future emotional experience (Doré et al, 2016; Lench et al, 2019; Levine et al, 2012). Despite being fairly accurate, participants in Study 1 overestimated the emotional impact of receiving a lower than expected grade or an expected grade, consistent with a large body of research showing an impact bias in affective forecasting (Gilbert et al, 2002; Wilson & Gilbert, 2003).…”
Section: Discussionsupporting
confidence: 92%
“…Undergraduates showed high accuracy when predicting the intensity of their feelings about receiving a better or worse exam grade than expected, but overestimated when asked to predict and later report their feelings in general [30]. Dore and colleagues [12] also document accuracy in predicting emotional intensity. They asked people to predict the intensity of emotion they would feel about the September 11, 2001, terrorist attacks 1, 2, or 7 years in the future.…”
Section: Similar Sources and Patterns Of Bias When Predicting And Remmentioning
confidence: 98%
“…Recent findings show that our mental GPS is not that bad. People often show striking accuracy when predicting the intensity of their feelings [12,29,30]. Predictions diverge most from experience when they encompass emotion duration or mood.…”
Section: Asymmetries Between Predicting and Remembering Emotionmentioning
confidence: 99%
See 2 more Smart Citations